Mexico - Wiemann, Kristina [Verfasser]; Botello Ramiréz, José Antonio [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2020)
"Mexico is an emerging nation with excellent basic demographic conditions. However, particular possibilities for economic and social development are only feasible if this potential can be exploited in an appropriate manner. Vocational education and training (VET) represents an important factor, but society’s low opinions of VET provision, as well as a weak connec tion between full-time school-based provision and demand in the labour market, pose challenges. The transition from school to employment is thus frequently made more difficult for graduates, while companies struggle to meet their own needs for skilled workers. Extensive reforms in the area of (vocational) education and training are intended to meet these challenges. One example is the introduction of a dual training model towards which German companies and stakeholders in VET cooperation arrangements can contribute. The title is part of the International Handbook of Vocational Education and Training, the standard reference for comparative research in vocational education in German. It is intended for an academic audience as well as vocational education and training practitioners. Selected titles are translated to make them available to the much broader English readership." ( Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.2.3.2 Anforderungen & Bedarfe; I 2.3.3 Lateinamerika; 370; Bildungssystem; Berufsbildungssystem; Rahmenbedingungen; Berufsbildung; Berufsverlauf; Berufliche Weiterbildung; Fachkräftemangel; Mexiko